Warning signs of injury: changes in pain, training load, and wellness in elite youth athletes - Lindman, I.; Abrahamson, J. (BMJ Open Sport & Exercise Medicine, 2026)
Background Injuries among youth athletes competing at an elite level are common. However, few studies have examined how training load, pain, and well-being develop in the weeks leading up to an injury. Understanding these factors may help in early identification and prevention of injuries.